1997
DOI: 10.1364/ao.36.001976
|View full text |Cite
|
Sign up to set email alerts
|

Neutral points in an atmosphere–ocean system 1: Upwelling light field

Abstract: We have developed a Monte Carlo code that utilizes the complete Stokes vector to examine the structure of the degree of linear polarization in the complete observable solid angle at any level in an atmosphere-ocean system. By performing these calculations we are able to compute the positions of neutral points in the upwelling light above and beneath the ocean surface. The locations of these points in a single-scatter calculation and a Monte Carlo treatment are shown for various conditions. The presence of aero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…Using this technique for measuring the first three Stokes parameters, we apply the method described in Adams and Gray [8] to identify neutral points and to determine their approximate location in observed scenes. We further comment upon these first reported observations of the neutral points predicted in the upwelling light field above a water surface by Adams and Kattawar [4] and discuss their qualitative agreement with these observations. These observations were made in the summer of 2011 from a pier on the Potomac River at the National Harbor in Maryland.…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations
“…Using this technique for measuring the first three Stokes parameters, we apply the method described in Adams and Gray [8] to identify neutral points and to determine their approximate location in observed scenes. We further comment upon these first reported observations of the neutral points predicted in the upwelling light field above a water surface by Adams and Kattawar [4] and discuss their qualitative agreement with these observations. These observations were made in the summer of 2011 from a pier on the Potomac River at the National Harbor in Maryland.…”
Section: Introductionsupporting
confidence: 63%
“…In our earlier paper [4], we showed that, in a simulated atmosphere-ocean system, neutral points would appear in the upwelling light field outside the principal plane. The way in which we presented the simulated light field was to show the quantities of interest in a fish-eye lens view projection.…”
Section: Observations Of Neutral Points Outside the Principal Plane Imentioning
confidence: 83%
See 2 more Smart Citations
“…We have recently done some simulations that show that if a Rayleigh scattering layer is placed on a highly forward scattering layer, the neutral points can also move off the principal plane. The observations by Soret and Cornu are the only two observations that we are aware of in which the neutral points were found off the principal plane in downwelling skylight, but calculations have shown neutral points for upwelling light above an ocean surface that were significantly away from this plane [35], and these have been observed in POLDER data [36]. Experimental results showing neutral points in the upwelling subsurface marine light field, significantly off the principal plane, were obtained by Voss et al [37].…”
Section: Neutral Points In the Oceanmentioning
confidence: 89%